The Importance of Physical Therapy in the Treatment of Legg-Calve-Perthes Disease - Silviu Gabriel Cioroiu (Editura Universitatii Transilvania din Brasov, 2022)
The article is based on the importance of applying the means and methods specific to physical therapy in the improvement of Perthes disease. The condition is known as Perthes, Legg-Perthes, or Legg-Calve-Perthes disease. Perthes disease is an avascular osteonecrosis of the epiphysis of the femoral head. It is assumed that through a kinetotherapeutic program appropriate to the patient's particularities, the mobility of the coxofemoral joint will remain within normal parameters, the femoral head will acquire a rounded shape, the stability of the joint will increase, walking will improve, and surgical intervention will be avoided or at least delayed.